Design, synthesis, and unraveling the antibacterial and antibiofilm potential of 2-azidobenzothiazoles: insights from a comprehensive in vitro study - Qadir, Tanzeela; Kanth, Saadat A.; Aasif, Mohammad; Fadul, Abdalla N.; Yatoo, Gulam N.; Jangid, Kailash; Mir, Mushtaq A.; Shah, Wajahat A.; Sharma, Praveen K. (Frontiers in Chemistry, 2023)
The present study reports the synthesis of 2-azidobenzothiazoles from substituted 2-aminobenzothiazoles using sodium nitrite and sodium azide under mild conditions. All the synthesized compounds were examined for their antibacterial activity against Gram (+) bacteria, Staphylococcus aureus (ATCC 25923), Enterococcus faecalis (ATCC 51299), Bacillus cereus (ATCC 10876) and Gram (-) bacteria, Escherichia coli (ATCC 10536), Pseudomonas aeruginosa (ATCC 10145), Klebsiella pneumonia (ATCC BAA-2146)and clinical isolates of Gram (+) Methicillin Resistant Staphylococcus aureus (MRSA) and Multi Drug Resistant Escherichia coli. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values by broth dilution method revealed that compound 2d exhibited significant antibacterial potential against Enterococcus faecalis and Staphylococcus aureus with MIC of 8µg/mL, while other synthesized compounds had only moderate effects against all the tested species. The compound significantly inhibited the biofilm formation of the bacterial strains below its MIC. The selective cytotoxicity of Compound 2d towards bacterial cells was evidenced on extended exposure of Human Embryonic Kidney-293 cell line to higher concentrations of the compound. Hence, the present study confirmed that compound 2d can be a potential drug candidate for future development as an antibacterial drug.